Secretomotor function of the dorsal motor nucleus of the vagus - Kerr, F. W. L. (1969)
1. The effect of chronic ablation of the dorsal motor nucleus of the vagus on insulin-induced secretion of acid by the stomach has been investigated in conscious cats. 2. Destruction of this nucleus results in a persistent profound reduction in gastric secretion of acid under these experimental conditions, while the visceromotor and cardioinhibitory effects of stimulation of the distal end of the acutely transected ipsilateral cervical vagus were unaffected. 3. It is concluded that the dorsal motor nucleus is a secretomotor centre.